Blood component ridable and CD44 receptor targetable nanoparticles based on a maleimide-functionalized chondroitin sulfate derivative. (15th February 2020) - Lee, Jae-Young; Lee, Han Sol; Kang, Nae-Won; Lee, Song Yi; Kim, Dong Hyun; Kim, Sungyun; Yoon, In-Soo; Cho, Hyun-Jong; Kim, Dae-Duk
Highlights: Maleimide group was introduced to nanocarrier for reaction with cellular thiol group. That reaction provided temporary cellular binding and improved tumor penetration. It may act as a new active tumor targeting strategy for precise cancer therapy. Abstract: Chondroitin sulfate A-deoxycholic acid-polyethylene glycol-maleimide (CSA-DOCA-PEG-MAL; CDPM) nanostructures were designed for the transient binding of MAL with thiol in blood components and cell membranes, in addition to the CD44 receptor targeting, for the therapy of breast cancer. The spontaneous binding of free thiol groups in plasma proteins and blood cells with the MAL group of CDPM was significantly higher than that of CSA-DOCA-PEG (CDP). Enhanced cellular uptake and the in vitro antiproliferation efficacy of docetaxel (D)-loaded CDPM (CDPM/D) nanoparticles (NPs) in MCF-7 cells indicated dual-targeting effects based on MAL-thiol reactions and CSA-CD44 receptor interactions. Following intravenous injection in rats, reduced clearance and an elevated half-life of the drug was observed in the CDPM/D NPs compared to the CDP/D NPs. Taken together, MAL modification of CDP NPs could be a promising approach not only to enhance tumor targeting and penetration but also to extend the blood circulation time of anticancer drugs.